A MATLAB code for recognition and counting of track images - Patiris, D. L.; Blekas, K.; Ioannides, K. G. (HNPS Advances in Nuclear Physics, 2019)
A computer program named TRIAC written in MATLAB has been developed for track recognition and track parameters measurements from images of Solid State Nuclear Track Detectors CR39. The program using image analysis tools counts the number of tracks and classifies the tracks according to their radii. Comparison of manual scanning counts with those output by the automatic system are presented for detectors exposed to a radon rich environment. The system was also tested to differentiate tracks recorded by alpha particles of different energies